Bacterial flora of the nasopharynx and nose - ARAI, Tatuhiko; IMAI, Akio; GOTOU, Akira; TOMIYAMA, Michio; TANAKA, Hisao; NAKANO, Yuichi (OTOLOGIA FUKUOKA, 1988)
Nasopharyngeal specimens were taken from 212 children attending the Akita Red Cross Hospital from April 1986 to March 1987. The study was designed to compare the nasopharyngeal and nasal flora in children with acute inflammatory otorhinolaryngological diseases to the nasopharyngeal and nasal flora in children without such observable diseases. In this report, the subjects were limited to those children who had no prior episodes of secretory otitis media. Results show that H. influenzae was found more frequently in children with acute inflammatory diseases of the ear, nose, and throat than in children without such diseases.